Prediagnostic non-steroidal anti-inflammatory drug use and survival after diagnosis of colorectal cancer - Coghill, Anna; Newcomb, Polly A.; Campbell, Peter T.; Burnett-Hartman, Andrea N.; Adams, Scott V.; Poole, Elizabeth M.; Potter, John D.; Ulrich, Cornelia (Gut, 2011)
Objective Non-steroidal anti-inflammatory drug (NSAID) use decreases both the incidence of colorectal cancer and recurrence of adenomas among patients with prior colorectal neoplasia. However, few studies have investigated the association between NSAID use and colorectal cancer-specific survival. The role of prediagnostic NSAID use was therefore examined in relation to colorectal cancer-specific survival among cases from the Seattle Colon Cancer Family Registry (Seattle Colon CFR). - Methods This was a follow-up study that included incident cases of colorectal cancer from the Seattle Colon CFR. Cases were aged 20-74, diagnosed from 1997 to 2002, and were identified using the population-based Puget Sound SEER registry. Detailed information on history of NSAID use, including type, recency and duration, was collected through an interviewer-administered questionnaire. Follow-up for mortality was completed through linkages to the National Death Index. The main outcome measure was death due to colorectal cancer after diagnosis. Cox proportional hazards regression was used to investigate the relationship between prediagnostic NSAID use and colorectal cancer-specific mortality among cases. - Results NSAID use prior to colorectal cancer diagnosis was associated with an ∼20% lower rate of colorectal cancer mortality after diagnosis compared with never use (HR 0.79; 95% CI 0.65 to 0.97). This relationship appeared to be duration dependent, with longer reported use prior to diagnosis associated with lower rates of colorectal cancer mortality among cases. The most pronounced reductions in mortality were observed among cases diagnosed with proximal disease (HR 0.55; 95% CI 0.37 to 0.82), whereas no association was observed between NSAID use prior to diagnosis and colorectal cancer-specific mortality among cases diagnosed with distal or rectal disease. - Conclusions The findings suggest that regular use of NSAIDs prior to diagnosis is associated with improved colorectal cancer survival, particularly among cases diagnosed with proximal disease and in longer term NSAID users.
Published online first 4 November 2010
Gesehen am 04.04.2022